Development of animated videos in social science learning for fourth-grade elementary schools - Faber, Faber; Erlisnawati, Erlisnawati; Syahrilfuddin, Syahrilfuddin; Marhadi, Hendri; Noviana, Eddy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This study aims to develop an animated video media for fourth grade social studies learning about economic diversity in Riau. This research is research and development with the 4D model, namely define, design, development and dissemination. The instruments used to obtain data were questionnaires (validation questionnaires and response questionnaires) and interviews. While the data obtained came from 2 validators, namely material experts and media experts, as well as 1 practitioner (teacher) and 12 students from one of the public elementary schools in Pekanbaru. Data collection techniques used were validity questionnaires, teacher response questionnaires, student responses and interviews. The results showed that the animated video media developed received very valid criteria with a proportion of 96.4% from material experts in the very valid category and very valid criteria with a score of 84.5% from media experts. The results of the teacher's answers get a very good score with a score proportion of 89.2%, one-to-one test results get a very good score with a score proportion of 90% and small group test results get a very good score with a proportion of 83.8%. It can be interpreted that animated video media is feasible and valid for use in learning.